PERSEPSI GURU TERHADAP PEMBELAJARAN ILMU HADITH DI SEKOLAH-SEKOLAH MENENGAH KEBANGSAAN AGAMA (SMKA) DI SERAWAK, MALAYSIA - Temrin, Maulana Muhammad Ilyas; Muhamed Ali, Mohd Akil (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2017)
Sekolah Menengah Kebangsaan Agama (SMKA), which was originally established by the Ministry of Education in 1977 is one of the important institutions at the secondary school level in the development of Islamic studies at Malaysia. Learning the hadith, as a major part of Islamic studies, is very important because hadith is a major source of Islamic teachings. Previous studies show that there are problems that occur during the learning process hadith studies at various institutions, including at the secondary school. Therefore, this study will identify teachers' perception of learning hadith studies in school, problems that occur in the learning process and proposals to solve the problem. This study will use a questionnaire that was distributed to each of the respondents (teachers) at their respective schools. The data obtained will be processed by means of descriptive analysis of frequency, percentage, mean and standard deviation through software Statistic Package for Social Sciences (SPSS) version 23. The research findings show that the methodology of learning the hadith taught by teachers reach a high-value interpretation. However, problems occur during the learning process hadith is the lack of use of teaching aids, such as books translation of the Arabic original books of hadith. Therefore, in order for the learning of hadith among these students could be improved it is necessary to update the existing syllabus, duplicate references in learning and teaching aids to reproduce the exciting and creative able to increase the interest of students in the study of hadith.